Complexes with Tunable Intramolecular Ferrocene to Ti-IV Electronic Transitions: Models for Solid State Fe-II to Ti-IV Charge Transfer - ALTUN, ZİKRİ (AMER CHEMICAL SOC, 2016)
Iron(II)-to-titanium(IV) metal-to-metal-charge transfer (MMCT) is important in the photosensitization of TiO2 by ferrocyanide, charge transfer in solid-state metal-oxide photocatalysts, and has been invoked to explain the blue color of sapphire, blue kyanite, and some lunar material. Herein, a series of complexes with alkynyl linkages between ferrocene (Fc) and Ti-IV has been prepared and characterized by UV-vis spectroscopy and electrochemistry. Complexes with two ferrocene substituents include Cp2Ti(C(2)Fc)(2), Cp*Ti-2(C(2)Fc)(2), and Cp2Ti(C(4)Fc)(2). Complexes with a single ferrocene utilize a titanocene with a trimethylsilyl derivatized Cp ring, Cp-TMS, and comprise the complexes (Cp2Ti)-Cp-TMS(C(2)Fc)(C2R), where R = C6H5, p-C6H4CF3, and CF3. The complexes are compared to Cp2Ti(C2Ph)(2), which lacks the second metal. Cyclic voltammetry for all complexes reveals a reversible Ti-IV/III reduction wave and an Fe-II/III oxidation that is irreversible for all complexes except (Cp2Ti)-Cp-TMS-(C(2)Fc)(C2CF3). All of the complexes with both Fc and Ti show an intense absorption (4000 M-1 cm(-1) < epsilon < 8000 M-1 cm(-1)) between 540 and 630 nm that is absent in complexes lacking a ferrocene donor. The energy of the absorption tracks with the difference between the Ti-IV/III and Fe-III/II reduction potentials, shifting to lower energy as the difference in potentials decreases. Reorganization energies, lambda, have been determined using band shape analysis (2600 cm(-1) < lambda < 5300 cm(-1)) and are in the range observed for other donor-acceptor complexes that have a ferrocene donor. Marcus-Hush-type analysis of the electrochemical and spectroscopic data are consistent with the assignment of the low-energy absorption as a MMCT band. TD-DFT analysis also supports this assignment. Solvatochromism is apparent for the MMCT band of all complexes, there being a bathochromic shift upon increasing polarizability of the solvent. The magnitude of the shift is dependent on both the electron density at Ti-IV and the identity of the linker between the titanocene and the Fc. Complexes with a MMCT are photochemically stable, whereas Cp2Ti(C2Ph)(2) rapidly decomposes upon photolysis.
Keywords: DENSITY-FUNCTIONAL THEORY; SENSITIZED SOLAR-CELLS; GENERALIZED GRADIENT APPROXIMATION; NONLINEAR-OPTICAL PROPERTIES; EXCITED-STATES; REDUCTIVE ELIMINATION; REACTION CHEMISTRY; SOLVENT POLARITY; METAL-COMPLEXES; VISIBLE-LIGHT